MODEL KOMUNIKASI PEMBANGUNAN PERIKANAN DALAM PEMBERDAYAAN KOMUNITAS NELAYAN SUKU DUANO DI PROPINSI RIAU (Analisis Program Marine and Coastal Resources Managemen Project di Propinsi Riau) - Zulkarnain ' (Berkala Perikanan Terubuk, 2011)
This artikel aimed to explain and analysis about model of communication fisheriesdevelopment in Duano Community in Riau Province, the advantage of this paperis to give information about how to compile the policy of fisheries development inRiau Province. The analysis model of communication fisheries development isneeded to implementation for the prosperity of fisherman. The Develop of ruralcommunity specially fishermen society needed by the integrity principal andpartisipative approach. this Partisipative approach through effort move grouporganization structures most elementary at the same time with its participation todevelop of them and theirs environment. Integrity principle have a meaning ofvertical and horizontal.